GABAA receptors and neuroligin 2 synergize to promote synaptic adhesion and inhibitory synaptogenesis - Sui, Yusheng; Mortensen, Martin; Yuan, Banghao; Nicholson, Martin W.; Smart, Trevor G.; Jovanovic, Jasmina N. (Frontiers in Cellular Neuroscience, 2024)
GABAA receptors (γ-aminobutyric acid-gated receptors type A; GABAARs), the major structural and functional postsynaptic components of inhibitory synapses in the mammalian brain, belong to a family of GABA-gated Cl -/HCO3 -ion channels. They are assembled as heteropentamers from a family of subunits including: α(1-6), β(1-3), γ(1-3), δ, ε, π, θ and ρ(1-3). GABAARs together with the postsynaptic adhesion protein Neuroligin 2 (NL2) and many other pre-and post-synaptic proteins guide the initiation and functional maturation of inhibitory GABAergic synapses. This study examined how GABAARs and NL2 interact with each other to initiate the formation of synapses. Two functionally distinct GABAAR subtypes, the synaptic type α2β2γ2-GABAARs versus extrasynaptic type α4β3δ-GABAARs were expressed in HEK293 cells alone or together with NL2 and co-cultured with striatal GABAergic medium spiny neurons to enable innervation of HEK293 cells by GABAergic axons. When expressed alone, only the synaptic α2β2γ2-GABAARs induced innervation of HEK293 cells. However, when GABAARs were co-expressed with NL2, the effect on synapse formation exceeded the individual effects of these proteins indicating a synergistic interaction, with α2β2γ2-GABAAR/NL2 showing a significantly greater synaptogenic activity than α4β3δ-GABAAR/NL2 or NL2 alone. To investigate the molecular basis of this interaction, different combinations of GABAAR subunits and NL2 were co-expressed, and the degree of innervation and synaptic activity assessed, revealing a key role of the γ2 subunit. In biochemical assays, the interaction between the NL2 and α2β2γ2-GABAAR was established and mapped to the large intracellular domain of the γ2 subunit.